2016
DOI: 10.18484/2305-0047.2016.3.240
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of Radiological Methods in Assessment of Inflammatory Activity and Fibrous Transformation of the Pancreas at Chronic Pancreatitis

Abstract: Цель. Изучить валидность лучевых методов диагностики в оценке активности воспаления и степени фиброзной трансформации поджелудочной железы при хроническом панкреатите. Материал и методы. У 98 пациентов проведено сопоставление результатов лучевых (КТ, УЗИ, соноэластография и соноэластометрия в режиме Shear Wave Elastography) методов исследования с данными морфологической оценки биоптатов поджелудочной железы (ПЖ), полученных во время хирургических вмешательств в связи с осложнениями хронического панкреатита (ХП… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
1
0
2
Order By: Relevance
“…Numerous investigations on the Surgery treatment of chronic pancreatitis are devoted to the choice of the most effective method of Surgery treatment, in particular, to various modifications of previously developed operations (Hamanou et al, 2002). As a rule, such long-term indicators of efficiency as control of a pain syndrome and exo-, the endocrine function of the pancreas are compared between groups of patients stratified first of all by type of Surgery intervention (Shevchenko et al, 2016). However, in a meta-analysis and systematic review, Zhao et al (2017), have concluded that although duodenal resections of the pancreatic head have advantages over pancreatoduodenal resection about the duration of the surgery, needs for blood transfusions, duration of hospitalization, weight gaining, and slightly better exocrine function in the long-term period, however, all operations were equally effective in terms of pain control, postoperative complications, endocrine, and exocrine insufficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous investigations on the Surgery treatment of chronic pancreatitis are devoted to the choice of the most effective method of Surgery treatment, in particular, to various modifications of previously developed operations (Hamanou et al, 2002). As a rule, such long-term indicators of efficiency as control of a pain syndrome and exo-, the endocrine function of the pancreas are compared between groups of patients stratified first of all by type of Surgery intervention (Shevchenko et al, 2016). However, in a meta-analysis and systematic review, Zhao et al (2017), have concluded that although duodenal resections of the pancreatic head have advantages over pancreatoduodenal resection about the duration of the surgery, needs for blood transfusions, duration of hospitalization, weight gaining, and slightly better exocrine function in the long-term period, however, all operations were equally effective in terms of pain control, postoperative complications, endocrine, and exocrine insufficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Основна маса досліджень з приводу хірургічного лікування хронічного панкреатиту (ХП) присвячена вибору найбільш ефективного методу оперативного лікування, особливо різним модифікаціям раніше розроблених операцій. Зазвичай порівнюються такі віддалені показники ефективності, як контроль больового синдрому та екзо-, ендокринна функція підшлункової залози (ПЗ) між групами хворих, стратифікованими в першу чергу за видом операції [1]. Однак у метааналізі та систематичному огляді Xin Zhao та співавт.…”
Section: вступunclassified
“…Выполнение дренирующих оперативных вмешательств на ПЖ и ее главном протоке приводит к ликвидации гипертензии в вирсунговом протоке и устранению болевого синдрома, но сохраняющиеся и усиливающиеся фиброзновоспалительные изменения в области головки ПЖ, а также наличие кальцификатов в паренхиме поджелудочной железы являются причиной развития осложнений, которые требуют выполнения более сложных резекционных вмешательств [3,4].…”
unclassified